A Study on Assessment of Clinical Education Standards of an Indian Government Dental College by Students (Journal of Orofacial Research, 2021)
Background: Dental education system lays the foundation of the professional life of dentists. The Indian dental education systemfaces many challenges; less importance to students’ opinions, health system challenges and political uncertainties. The aim of thisstudy was to compare the opinions of dental students regarding their clinical education system and to identify the advantages and disadvantages of the clinical education system. Materials and Methods: Clinical Education Instructional Quality questionnaire(ClinED IQ) was used. It allows assessment of qualitative and quantitative information on student perceptions of clinical teachingskills of faculty and other factors. Undergraduate dental students attending clinics (3rd year (n=30), 4th year (n=30) and interns(n=34)) participated in the study. Results: 87% students felt they had experienced a good mix of patients, problems, and clinicalexperiences (p=0.019). 56% felt diverse learning opportunities and mix of patients, preventing them from developing proficiency(p=0.032). Eighty-eight percent of students felt improvement in their communication and skills (p=0.025) with the patient.Students significantly felt that sometimes time is wasted with non-educational tasks. (p=0.030), and they did not feel a usefulmember of the health care team (p=0.024). A statistically significant number of students felt discouraged from taking risks ortrying new things (p=0.017). Conclusion: Students experience a good mix of clinical learning opportunities however they do notfeel involved as a part of health care team. Their time gets wasted in many non-clinical activities. Modifications are required in thepresent education system giving more importance to student’s perspectives.